Appropriate prescribing of antiemetics with oral oncolytic therapy: a single center experience. (3rd September 2019) - Suen, Connie T.; Hughes, Mitchell E.; Timlin, Colleen; Cambareri, Christine; Kriska, Richard; Strong, Gregory; Favatella, Joseph K.; Demers, Richard; Capozzi, Donna L.
Abstract: Background: Chemotherapy-induced nausea and vomiting (CINV) is a common and significant side-effect of chemotherapy that can impact a patient's quality-of-life (QoL). As oral oncolytic therapies (OOT) become a common treatment option, they pose unique challenges for providers and patients. Unlike infusion therapies, a single-day administration, OOT may require daily dosing during a treatment cycle and, therefore, require patients to be proactive in terms of supportive care monitoring and prevention. The American Society of Clinical Oncology provides recommendations for appropriate emetic prophylaxis, however, due to limited data for OOT, only offer recommendations for single-day IV chemotherapy. Aims: The objective of this quality improvement study was to review the appropriate prescribing of antiemetics with OOT, in the specialty and ambulatory setting, and evaluate the opportunity to enhance medication safety and improve vigilance of concurrent prescribing with pharmacist involvement. Methods: All patients ordered for OOT between January and December 2018 to the Hospital of the University of Pennsylvania specialty pharmacy were reviewed for concurrent antiemetic prescriptions. Patients were excluded if prescriptions were sent to a satellite or outside institution pharmacy. Patients who were identified to have a discordant antiemetic:OOT prescribing ratio were evaluated for adverse events such as CINC-related office visits or hospitalization; as documented in the electronic medical record. Results: A total of 1, 630 OOT prescriptions were written for 354 patients. Two hundred and sixty-eight patients were excluded for the following reasons; 117 (33.0%) were prescribed to a satellite or outside pharmacy and 151 (42%) had concordant antiemetics. Eighty-six patients were included based on initial discordance given that OOT and antiemetics were not ordered within the same office visit. Upon further evaluation, 60 were found to have active antiemetics ordered as part of a previous line of therapy and, therefore, had an adequate supply. Of the n  = 26 without antiemetics, n  = 4 were deemed to not require antiemetics, while n  = 22 were confirmed to lack prescriptions. There were no reports of CINV that required urgent care or hospitalizations. Conclusions: OOT is becoming increasingly common, with unique risks such as CINV. The authors plan to increase the pharmacist involvement with the prescribing and counseling of new OOT to promote improved supportive care measures, communication between patients and providers, and potential avoidance of patient harm and improved QoL.